2016
DOI: 10.1007/s10483-016-2095-9
|View full text |Cite
|
Sign up to set email alerts
|

Mode transition and oscillation suppression in supersonic cavity flow

Abstract: Supersonic flows past two-dimensional cavities with/without control are investigated by the direct numerical simulation (DNS). For an uncontrolled cavity, as the thickness of the boundary layer declines, transition of the dominant mode from the steady mode to the Rossiter II mode and then to the Rossiter III mode is observed due to the change of vortex-corner interactions. Meanwhile, a low frequency mode appears. However, the wake mode observed in a subsonic cavity flow is absent in the current simulation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The effect of the boundary layer thickness on the pressure oscillation and mode transition for uncontrolled supersonic cavity flows was studied in our previous work. 33 Here, we performed three simulation cases, and the flow conditions are listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the boundary layer thickness on the pressure oscillation and mode transition for uncontrolled supersonic cavity flows was studied in our previous work. 33 Here, we performed three simulation cases, and the flow conditions are listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous works 33,45 have reported that the flow mode in supersonic cavity flows could be divided into the steady mode, the shear layer mode (the Rossiter mode), and the wake mode. The dash-dot and dashed lines in Figure 7 show the oscillation frequencies of the Rossiter modes based on equations ( 4) and ( 5), respectively, and m = 1-4.…”
Section: Flow Mode Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD numerical simulation mainly includes direct numerical simulation (DNS) [12][13][14], Reynolds averaged Navier-Stokes (RANS) [15,16], and large eddy simulation (LES) [17][18][19]. DNS is a direct high-fidelity method for solving Navier-Stokes equations, which requires very fine grids.…”
Section: Introductionmentioning
confidence: 99%